Development of morphological technique for segmentation of anatomical objects in abdominal MRI - Sarker, S. Z.; Tan, W. H.; Logeswaran, R. (MANEY PUBLISHING, 2008)
In this paper, a morphological technique for the segmentation of abdominal organs in magnetic resonance imaging (MRI) images is proposed based on watershed segmentation. New morphological based preprocessing and post-processing techniques are developed to reduce oversegmentation by means of removing and merging spurious segments. The preprocessing aims at removing trivial regions as well as background noise by combining thresholding, morphological smoothing, Gaussian smoothing and morphological edge detection. To obtain a more concise region representation, the watershed segmented image is post-processed, where a region adjacency list is built for the region merging process that produces the final segments. To control the merging process, a similarity function is defined, whence the most similar neighbouring regions are merged. The proposed technique produces effective and significant results in successfully segmenting various anatomical objects in axial MRI images of the abdomen, as it is shown in this paper.